KETIKA MOHAMMED ARKOUN MEMBINCANG WAHYU - el-Mawa, Mahrus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
Expressing of somebody's thought is like open a window of ideas world on a period. Terminology of